On collective intelligence - Theo, Bastiaens; Baumöl, Ulrike; Krämer, Bernd J. (Berlin Springer, 2010)
Welcome to the proceedings of the inaugural Symposium on Collective Intelligence (COLLIN 2010). This was the first of a new series of events that will evolve over the coming years, and we were happy to hold the event in Hagen where the idea for this symposium was born. The participants visited Hagen in April, with excellent opportunities to get rain, wind and sun. Collective intelligence denotes a phenomenon according to which the purposeful interaction between individuals creates intelligent solutions and behaviors that might not have come to existence without this concerted effort of a community. The members of such communities form a social network, typically over the Internet. They are engage with each other over a sustained period of time to develop an area of innovation through collaboration and exchange of ideas, experiences and information. Leading-edge information and communication technologies (ICT) offer ample opportunities for enabling collective intelligence. COLLIN aims to become the flagship conference in the areas collective intelligence and ICT-enabled social networking, which is attracting more and more researchers and practitioners from both academia and industry.
Preface.-On Collective Unintelligence.-Building actor reputation in web-based innovation networks An approach for the visual representation of business models that integrate web-based collective intelligence into value creation.-Open Science 2.0: How Research and Education can benefit from Open Innovation and Web 2.0 -- A Social Network System for Analyzing Publication Activities of Researchers.-Use of Swarm Intelligence to Include Customers in Product Innovation.-Imitation and Quality of Tags in Social Bookmarking Systems Collective Intelligence Leading to Folksonomies.-Measuring and Analyzing the Openness of the Web 2.0 Service Network for Improving the Innovation Capacity of the Web 2.0 System through Collective Intelligence -- Collective Intelligence in Teams Practical Approaches to Develop Transactive Memory.-The Need Language.-Adding Taxonomies Obtained by Content Clustering to Semantic Social Network Analysis.-How to reduce new product development: Customer Integration in the e-fashion market.
Keywords: Swarm intelligence -- Congresses; Online social networks -- Congresses; Communication -- Technological innovations -- Congresses; Electronic books